2016
DOI: 10.1097/meg.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

A proof-of-concept study showing antibiotics to be more effective in irritable bowel syndrome with than without small-intestinal bacterial overgrowth

Abstract: Norfloxacin is superior to placebo in relieving symptoms of SIBO-associated IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 29 publications
1
74
1
1
Order By: Relevance
“…We identified nine trials, reported in eight separate papers, [90][91][92][93][94][95][96][97] which evaluated antibiotic therapy in 2845 patients with IBS (Figure 6). Detailed trial characteristics are provided in Table 3.…”
Section: Efficacy and Safety Of Antibiotics In Ibsmentioning
confidence: 99%
“…We identified nine trials, reported in eight separate papers, [90][91][92][93][94][95][96][97] which evaluated antibiotic therapy in 2845 patients with IBS (Figure 6). Detailed trial characteristics are provided in Table 3.…”
Section: Efficacy and Safety Of Antibiotics In Ibsmentioning
confidence: 99%
“…A causative role of SIBO in IBS has been established by Koch's postulates 27 . Moreover, three recent studies, one from India, 28 one from China, 29 and the most recent one from USA, 30 showed that response of IBS patients with SIBO to treatment with antibiotics is far greater than when antibiotics are used without testing for SIBO. These studies suggest that in future, treatment of IBS patients may see a paradigm shift with a more personalized or individualized approach somewhat similar to several other fields of medicine.…”
Section: Gut Microbiota Dysbiosis In Irritable Bowel Syndromementioning
confidence: 99%
“…However, these may work through different mechanisms in different subtypes of IBS patients. For example, three studies showed that antibiotics are more often effective in patients with IBS‐D with SIBO than those without SIBO 28–30 . In patients with IBS‐C, rifaximin with or without neomycin works primarily by targeting methanogens, which, by producing methane, slow colon transit.…”
Section: Pathophysiology‐directed Treatment For Irritable Bowel Syndromementioning
confidence: 99%
“…Though in the past, tetracycline, doxycycline, co-trimoxazole, fluoroquinolones have all been used in the treatment of SIBO,109,110 in most of the recent studies among patients with IBS, rifaximin has been the preferred antibiotic (Table 2). 52,108,111114…”
Section: Treatment Of Sibo In Patients With Ibsmentioning
confidence: 99%